POTENTIAL SOURCES OF MERCURY IN SOUTHERN PATTANI BASIN, THE GULF OF THAILAND - Rattanasriampaipong, Ronnakrit (Bulletin of Earth Sciences of Thailand, 2021)
Potential sources of mercury in producing oil and gas fields can be from either geogenic (hydrothermal fluid migration, coals and carbonaceous shales, etc.) or anthropogenic (water re-injection activities) sources. Due to lack of knowledge on mercury occurrence in the petroleum systems in SE Asia, no conclusive explanation has yet been made for the variable, sometimes elevated mercury concentrations measured production fluids in wells in the Pailin area, southern Pattani Basin, offshore Thailand. In prior work, petroleum engineers attempted to identify likely Hg contributing zones by conducting detailed investiga-tions using dedicated platforms with known perforated pay zones based on geological marker correlation. But none of engineering work considered the possibility of documentation of geological controls. This current research project is the first attempt to integrate conventional geological approaches (cuttings, petrography, isotopes, wireline and seismic) with engineering datasets (mercury surveillance data, gas composition, production data) in order to better interpret and evaluate potential sources of mercury in the Pailin operating area. Based on the series of geological evaluations applied in this integration, the following conclusions are drawn as to the origin of the anomalous Hg levels; (1) There is a poor correlation between levels of Hg and deeply-sourced CO2 making a basement source less likely, (2) There is no obvious indication of hydrothermal fluid influence, based on the C-O isotopic signatures of various carbonate cements, specifically sampled from cuttings, (3) The low levels of reinjec-tion of produced water and a lack of correlation to this parameter across the area, means an anthropogenic cause for mercury-enriched hydrocarbons is unlikely, and (4) Intrabasinal geogenic sources, particularly from mature marginal marine coals and carbonaceous shales characterized by elevated levels of uranium, as indicated in spectral gamma ray log (“High Gamma Zones”), are considered the most likely source of elevated Hg Levels. Mature generating zones of this interval are most common in Upper Sequence 2 in the Gulf of Thailand (GOT) stratigraphy.This study concludes that mercury and its compounds were either sequestered in the remains of coalforming land plants or deposited in associated muddy marine-influenced swamp and transitional marine deposits, where organic matter accumulated in reducing environments. Then, as these rocks were buried and matured the mercury co-migrated with the expelled hydrocarbon from its source to its reservoirs.